Comparative monocyte and T cell responses in DENV-exposed subjects from South-East Asia and DENV-naïve residents in Taiwan - Sheng-Hsuan Wang; Yun-Erh Chuang; Sia-Seng Tan; Tzu-Chuan Ho; Oscar Guey Chuen Perng; Po-Lin Chen (Journal of Microbiology, Immunology and Infection)
Background/purpose(s): Dengue virus (DENV) is one of the most troublesome mosquito-borne infectious viruses in tropical and subtropical zones. People with secondary/multiple DENV infections are at an increased risk of developing severe dengue. Both monocytes and T cells are known to play important roles in the immune response against DENV. However, the function of monocytes and T cells in individuals with potentially multiple exposures to DENV is rarely reported. Method: In the present study, we performed a functional analysis of monocytes and T cells from people with previous DENV infection and DENV-naïve people that stimulated with DENV2 ex vivo. Results: Our preliminary analysis indicated that the response of monocytes and T cells to DENV2 restimulation was comparable between DENV-exposed and DENV-naïve individuals. Furthermore, the cytokine expression profiles in monocytes from both naïve individuals and previously DENV-exposed subjects were similar after DENV2 stimulation. In addition, it was observed that the function of T cells was also equivalent when monocytes were present as antigen-presenting cells for dengue antigen, NS3, in terms of cell proliferation, interferon-gamma (IFNγ) secretion, and memory response. Conclusions: Based on the results, it was observed that previously DENV-exposed monocytes and T cells seemed to be anergic during DENV reinfection. However, whether the impaired response of monocytes and T cells against DENV in people with a history of previous DENV infection leads to severe dengue upon secondary infection in endemic areas requires further investigation.